2011
DOI: 10.1111/j.1439-0531.2011.01759.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Parturition with Aglepristone in the Majorera Goat

Abstract: This study assessed the efficacy of aglepristone at inducing parturition in pregnant goats. Six experimental groups were defined: group A-5 (n = 12), group A-3.3 (n = 12), group A-2.5 (n = 12) and group A-1.5 (n = 12) in which goats were injected SC once with 5.0, 3.3, 2.5 and 1.5 mg of aglepristone per kg body weight of goat, respectively, group L (n = 11), which was treated IM with 3.75 mg of luprostiol; and group Ct (n = 11), which was injected SC with 1 ml of saline solution. Different parameters associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…In the current study, PGF 2α injection induced kidding within 29.00±11.37 hours . This compared favorably with the report of Batista et al (2011) in which induction occurred within 30 to 34 hours without any effect on foetal viability or the incidence of retained placenta. Placenta was expelled in the first 6 hours after the induced natural parturition.…”
Section: Discussionsupporting
confidence: 78%
“…In the current study, PGF 2α injection induced kidding within 29.00±11.37 hours . This compared favorably with the report of Batista et al (2011) in which induction occurred within 30 to 34 hours without any effect on foetal viability or the incidence of retained placenta. Placenta was expelled in the first 6 hours after the induced natural parturition.…”
Section: Discussionsupporting
confidence: 78%
“…At the 142nd gestation day, IP with dexamethasone synchronized parturition without dystocia (38). Repeated doses (15 mg/kg) of aglepristone or its combinations have been used for IP in dogs (19), and this drug has also been applied as a unique dose (5-3.3-2.5-1.5 mg/kg) in goats at the 145th gestation day for IP (3). Because the incidence of retained fetal membranes and neonatal mortality was high at a 1.5 mg/kg dose in goats (3), we used 2.5 mg/kg of aglepristone in combination with dexamethasone in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoid usage is a well-known conventional choice to terminate gestation in the veterinary field (1,5,26). Because progesterone plays a primary role in continuing gestation, the application of antiprogestine drugs (mifepristone or aglepristone) has been popular in recent studies (3,12,19,21).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one of these reviews, it was shown that congenital hyperplasia of the fetus resulting from disturbances in cortisol production causes post-term births. In some studies, an association has been observed between stress in the mother and premature childbirth [5] .…”
Section: Introductionmentioning
confidence: 99%